Solid waste public policies and environmental technological innovation: A narrative review on the implementation of reverse logistics (Research, Society and Development, 2024)
Objective: To analyze how public policies can be aimed at mitigating the challenges of implementing reverse logistics in developing countries, with an emphasis on sustainable innovation. Methodology: The Narrative Literature Review method was used to compose the state of the art through a search and selection of scientific articles in the Scientific Electronic Library Online, provided that they addressed the implementation of environmental public policies related to Reverse Logistics and sustainable innovation. Eleven articles were selected that met these criteria. Results: After reading, critically analyzing and synthesizing the materials researched and selected, the results found highlighted the importance of eco-innovation and sustainable engineering as tools to improve efficiency in waste management, proposing adjustments to public policies to overcome the barriers identified. Conclusion: the adoption of emerging technologies and the integration of cooperatives are essential strategies for strengthening reverse logistics and promoting sustainable practices, in line with the Sustainable Development Goals.